PHYTOCHEMICAL SCREENING AND ANTIMICROBIAL ACTIVITY OF LEUCAS MARRUBIOIDES DESF. ROOT EXTRACTS - Gowrish, A.; Vagdevi, H. M.; Rajashekar, H. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The number of multidrug-resistant microbial strains and the appearance of strains with reduced susceptibility to antibiotics forced scientists to search for new antimicrobial agents from plants. The present study was aimed to evaluate the phytochemical constituents and antimicrobial potential of Leucas marrubioides Desf. root extracts. Methods: The roots of L. marrubioides was extracted with solvents of varying polarity, namely pet-ether, chloroform, and methanol. The phytochemical screening was carried out qualitatively to identify the major phytoconstituents present in the extracts. The antimicrobial activity of extracts was evaluated against five Gram-positive bacteria, five Gram-negative bacteria and six fungal strains by agar well diffusion method. The Minimum Inhibitory Concentration (MIC) of the extracts was determined by Broth dilution method. Results: The results of the study indicated that the pet-ether and chloroform extracts of the plant were highly effective towards most of the Gram-positive, Gram-negative bacteria and fungal strains. While, the methanol extract was moderately active towards all the tested organisms. The pet ether extract had lowest MIC of 1.562 mg/ml against V. cholerae and Curvularia sp and chloroform extract had lowest MIC of 1.562 mg/ml against only C. neoformans. The methanol extract showed MIC of 1.562 mg/ml against the organisms S. pyogenes, C. neoformans and C. albicans. Conclusion: The potent antimicrobial activity against Gram-positive bacteria, Gram-negative bacteria and fungal strains may be due to the presence of broad spectrum antibiotic compound in the extracts. The study validates the use of the plant in the treatment of bacterial and fungal infections. Â 